Cash-For-Care, or Caring for Cash? The Effects of a Home Care Subsidy on Maternal Employment, Childcare Choices, and Children's Development - Matthias Collischon; Daniel Kühnle; Michael Oberfichtner (Institute of Labor Economics (IZA), 2020)
How parents respond to changes in the price of childcare is an important, though not fully understood, public policy question. Our paper provides new comprehensive evidence on how a home care subsidy jointly affects maternal labour market outcomes, childcare choices, and children's development. We examine a German reform from 2013 which introduced a home care subsidy of initially 100 Euros per month for families who do not use subsidised childcare. Exploiting a date-of-birth cut-off in eligibility and using administrative data on employment and child development alongside survey data on childcare usage, we show that the reform reduced mothers' likelihood to return to work within three years by only 1.4 percentage points, but decreased childcare enrolment for one- and two-year olds by 5 percentage points. We find no effect on children's skill development at age six. Our findings imply that the subsidy accrued almost completely as windfall gains to families who would not have used formal childcare anyway.
Keywords: J13; J18; J22; 330; childcare choices; maternal labour supply; cash-for-care; home care subsidy; children's development; windfalls gains